Effectiveness of Filters on the Growth and Survival Rate of Tambaqui (Colossoma macropomum) in a Recirculating Aquaculture System - Ahmad Sayyid Barokah; Iskandar Putra; Niken Ayu Pamukas (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Tambaqui (Colossoma macropomum) is a highly promising aquaculture commodity, yet intensive cultivation produces excessive organic waste that degrades water quality. The Recirculating Aquaculture System (RAS) serves as an effective solution for managing water quality through filtration, the performance of which depends heavily on the filter's design and layout. This study aimed to determine the effectiveness of various filter layouts on water quality stability, growth performance, and survival rates of tambaqui reared in a recirculating system. This experimental study employed a Completely Randomized Design (CRD) with 4 treatments and 3 replications, including layouts with no filter/control (P1), vertical (P2), horizontal (P3), and a vertical-horizontal combination (P4). The rearing process was conducted for 50 days at the Aquaculture Technology Laboratory, Universitas Riau. The results demonstrated that the combination filter layout (P4) yielded the best performance, achieving an average absolute weight gain of 10.71 g, absolute length gain of 6.81 cm, specific growth rate of 3.58%, feed efficiency of 83.33%, feed conversion ratio of 1.18, and a survival rate of 100%. Water quality parameters in P4 also exhibited the highest stability, with temperatures of 26.9–29.4°C, pH 6.1–7.3, dissolved oxygen 4.50–6.00 mg/L, ammonia 0.007–0.022 mg/L, nitrite 0.038–0.044 mg/L, and nitrate 0.131–0.366 mg/L. It can be concluded that the implementation of a recirculating system with a combination filter layout (vertical-horizontal) is the most effective treatment for optimizing water quality, thereby significantly enhancing the somatic growth and feed utilization efficiency of tambaqui.